Experimental Study of Miscible Fluid Injection in Fractured Porous Media - JAMSHIDNEZHAD, M.; RAHMATI, M. Montazer; SAJJADIAN, V.A. (Journal of Oleo Science, 2003)
Laboratory displacement tests were performed to study solvent cut by miscible fluid injection in fractured porous media.The porous media used were cylindrical Asmari sandstone cores containing a well-afined artificially formed, vertical fracture.Normal heptane and kerosene were two miscible fluids used.The purpose of this study was to compare the results from one-dimensional theory of miscible displacement in fractured porous media to experimental data.We observe that there is a good agreement between experiments and model predictions.